Runaway train : youth with emotional disturbance - Libal, Autumn (Broomall, Pa. : Mason Crest, 2004)
Tells the story of Sheila, a high school student suffering from severe emotional disturbance, and her attempts to cope by venting her rage, cutting herself, and starving herself before getting the help she needs to begin to recover.
Sheila's rage -- Trent's subterranean world -- The truth as he sees it -- Bloodletting -- Detected -- A cut too deep -- Runaway train -- Weathering the storm.
Includes bibliographical references (p. 121) and index.
Keywords: Behavior disorders in children -- Juvenile literature; At-risk youth -- Juvenile literature; Mentally ill children -- Juvenile literature; Problem children -- Juvenile literature; Adolescent psychotherapy -- Juvenile literature; Emotional problems; Adolescent psychology -- Juvenile literature